Rice production and regional crop diversification in the Philippines economic issues - Gonzales, L. A. (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1987)
The paper discusses Philippine rice production on the basis of some economic issues. Its main points are that 1) the current low world market price of rice adversely affects the economic viability of Philippine rice production, 2) Economic efficiency should be the overriding norm in attempts to alleviate the plight of the poor and disadvantaged groups, 3) Agricultural diversification can be tapped to help improve the economic well-being of poor rice farmers, 4) Given natural resource endowments, technology and trade, the determinant of agricultural diversification should be comparative advantage or economic efficiency.